CORE and Problem Bassed-Learning: The Impact on Critical Thinking Ability Based on Self Regulation - Bastian, Veri; Huda, Nizlel; Suratno, Suratno; Yudistira, Pengki (Universitas Islam Negeri Raden Intan Lampung, 2022)
The low ability to think critically can affect the student's learning process. In overcoming the problem of critical thinking, teachers must first observe students' self-regulation. This quasi-experimental study aims to determine the effect of the CORE and PBL models on students' critical thinking skills based on self-regulation and interactions. The population is all 8th grade students of SMP N 1 Tungkal Ulu. Random sampling technique was used to choose class VIII B as experimental class 1 with 34 students, VIII D as experiment class 2 with 32 students, and VIII E as control class with 33 students. Data were collected using test questions. Statistical test using two-way ANOVA with SPSS software version 21 with a confidence level of 0.05. The results of the study based on hypothesis testing in the three classes obtained that Fcount was 18.693 while the value of Ftable was 4.00, meaning that Fcount was greater than Ftable. These results indicate that H1 is accepted (there are differences in critical thinking). It was concluded that CORE and PBL learning had an effect on improving students' critical thinking skills compared to traditional learning. However, there is no interaction between learning treatment and critical thinking skills.